Sistem Pahala dalam Al-Qur'an: Analisis Tematik tentang Surga, Neraka, dan Perbuatan Manusia - Dea Destiani; Zulfa Intan Andromeda; Muhammad Alif (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The concepts of paradise and hell constitute the Qur'an's comprehensive system of divine reward and punishment, serving not only as descriptions of the afterlife but also as ethical mechanisms that shape human conduct. Despite extensive studies on Qur'anic eschatology, the relationship between paradise, hell, and human deeds as an integrated reward system remains insufficiently explored. This study aims to examine the Qur'anic reward system through a thematic analysis of paradise, hell, and their correspondence with human deeds. Employing a qualitative library research design, the study applies the Structured Thematic Analysis (STA) method, integrating thematic Qur'anic interpretation with systematic coding procedures adapted from Grounded Theory. The primary data consist of Qur'anic verses concerning paradise, hell, faith, and righteous deeds, supported by classical and contemporary Qur'anic commentaries. The findings demonstrate that the Qur'an constructs a hierarchical and proportional reward system grounded in divine justice. Paradise is portrayed through progressive levels of reward encompassing sensory, psychological, social, and transcendental dimensions, culminating in the vision of Allah (ru'yat Allāh), while hell presents graduated forms of punishment corresponding to varying degrees of disbelief, injustice, and sinful behavior across physical, psychological, and metaphysical dimensions. The analysis further reveals that reward and punishment operate at both individual and collective levels, reinforcing moral accountability within personal and social life. This study contributes to Qur'anic studies by conceptualizing the Qur'anic reward system as an integrated ethical framework linking faith, righteous deeds, divine justice, and eschatological accountability, thereby providing a comprehensive perspective for contemporary Islamic education and da'wah.